Russian Neologisms with Social Semantics: Features of Identification and Principles of Lexicography - A. V. Shchetinina (Научный диалог)
The study examines neological processes in the Russian language based on the utilization of its own resources. The novelty of the research lies in the typologization of this type of new Russian vocabulary within the thematic group “Society”. The material for the study consists of words and phraseologisms with institutional social semantics, which are included in the first volume of the new “Explanatory Dictionary of Russian Neologisms”, one of the compilers of which is the author of the article. A semantic characterization of new Russian words and phraseologisms is provided. It is noted that social semantics was identified both in the assertive part of the semanteme and on the near periphery, as well as in pragmatic presumption. The inclusion of words with not only Russian roots and affixes (the first part of the dictionary) but also with foreign roots and Russian affixes (the second part) is justified. It is indicated that the latter constitute a significant portion of the neologisms. Examples are given for describing different types of neological linguistic units. A fragment of the ideographic reconstruction of the lexical stock of Russian neologisms described in the first part of the dictionary is presented. The stylistic affiliation of the linguistic units included in the dictionary is analyzed. The conclusion is drawn about the stylistic blending when using neologisms in different types of discourse.